Service Animals - Boynton, Alice Benjamin (Egremont, Massachusetts : Red Chair Press, 2019)
"You know that pets can be fun. But some dogs, horses, pigs, and more have important jobs to do. With Animals That Help Us young readers will discover how animals help us stay safe. Service animals are uniquely trained to help when someone is not able to help themselves. Readers learn how and why monkeys are some of the most important service animals. Readers meet other service animals such as small horses, dogs, and birds."-
Animals at your service -- Monkey helpers -- Hearing dogs -- Guide horses -- Words to keep -- Learn more at the library -- Index.
Includes index
Keywords: Animals as aids for people with disabilities -- Juvenile literature; Working animals; Animals as aids for people with disabilities; Juvenile works; Juvenile literature